2000
DOI: 10.1259/bjr.73.866.10884729
|View full text |Cite
|
Sign up to set email alerts
|

False positive thallium-201 SPECT imaging in brain abscess.

Abstract: Three cases of intracranial 201Tl uptake, reported as positive tumour activity in patients with a final diagnosis of abscess, are described. 201Tl has been proposed as a useful oncotropic radiotracer in the diagnosis of brain tumour activity. These cases suggest a note of caution in the interpretation of 201Tl brain images in the differential diagnosis of an intracranial expanding mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…201 Tl single photon emission computed tomography (thallium SPECT) has been proposed as an indicator of both the histological grade of the tumour and prognosis of brain lesions. Other authors [18,19] did not confirm this correlation. Most recently, Gungor et al [2] showed that thallium uptake can predict proliferative activity of a glioma as defined by the proliferating cell nuclear antigen labelling index.…”
Section: Introductionmentioning
confidence: 80%
“…201 Tl single photon emission computed tomography (thallium SPECT) has been proposed as an indicator of both the histological grade of the tumour and prognosis of brain lesions. Other authors [18,19] did not confirm this correlation. Most recently, Gungor et al [2] showed that thallium uptake can predict proliferative activity of a glioma as defined by the proliferating cell nuclear antigen labelling index.…”
Section: Introductionmentioning
confidence: 80%
“…30) The intensity of radiotracer uptake in brain abscess is high, but lower than in malignant brain tumor. 3,21,25) The high uptake of 201 Tl in brain abscess is due to the presence of similar histological changes, including changes in bloodbrain barrier permeability, increased vascularity, and increased metabolic cellular activity. 21) Slight 201 Tl uptake specifically occurs in neutrophils and macrophages in inflammatory tissue.…”
Section: Discussionmentioning
confidence: 99%
“…3,21,25) The high uptake of 201 Tl in brain abscess is due to the presence of similar histological changes, including changes in bloodbrain barrier permeability, increased vascularity, and increased metabolic cellular activity. 21) Slight 201 Tl uptake specifically occurs in neutrophils and macrophages in inflammatory tissue. 3) We could differentiate pituitary abscess from pituitary adenoma in our case because the pituitary abscess showed homogeneous uptake by 201 Tl SPECT on both the early and delayed images without enhancement of the central portion on MR imaging.…”
Section: Discussionmentioning
confidence: 99%